Labeling dan Packaging Camilan PAY Mart untuk Kemandirian Ekonomi PAY Putri Aisyiyah Yogyakarta: PAY Mart Snack Labeling and Packaging for PAY Putri Aisyiyah Yogyakarta's Economic Independence - Lestari Rahayu; Nur Rahmawati; Diah Rina Kamardiani (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Packaging and labeling are important points in selling an item. Initially, the packaging functioned as a place to make it easier to carry a product. However, the packaging is needed over time to encourage buyers' buying interest. In planning the packaging, it is not only an initial plan but also an idea that can show the advantages of a product so that it shows a design that can